A Case Study of Academic Writing Development Through Principled Versus Standard Clt Method at Binus University - Almodad Biduk Asmani (Bina Nusantara University, 2013)
The purpose of the research project is to investigate how far the academic writing skills of Binus University students can be developed through two conflicting CLT methods: standard and principled. The research project is expected to result in computer-animated format which can be used as one of the main tools in teaching and learning grammar at Binus University. The research project uses the qualitative approach, and thus uses verbal data. The research project involves two subject groups (experimental and control). The experimental group will receive the treatment of grammar learning by using the Principled CLT approach, while the control group receives the standard CLT approach. Survey is then conducted to the two groups so as to find out their comments on the two teaching methods. From the results of the questionnaires, it is found that Principled CLT method is favored for its knowledge and accuracy factors, while the Standard CLT is preferred for its fun and independence factors.